On the modeling of flywheel rotor systems via unified formulation: Viability, practicalities, and experimental validation. (1st November 2022) - Del Claro, Vergílio T.S.; Cavalini, Aldemir Ap.; Santos, Ilmar F.; Steffen, Valder
Abstract: Recent times have seen a great interest on environmental issues and efficient, sustainable systems. This interest has required the employment of advanced composites for a myriad of industrial machines and innovative equipments. Among these applications, Flywheel Energy Storage Systems – FESS – represent a group of machines that are being re-invented through this process. Modeling composite flywheels has proven to be a complex task, which current Finite Element models fail to fulfill in a number of design contexts. This demand to model complex composite geometries and systems induced the proposition of new methods, aiming to capture the various physical effects existing in the problem. In the present contribution, the authors consider that it is viable to model the dynamic behavior of a Flywheel Energy Storage System via an adapted Carrera Unified Formulation, both in terms of accuracy and computational cost, for practical applications. The present work presents and explores a Carrera Unified Formulation model with extended capabilities dedicated to rotordynamics applications. The differences from standard Finite Elements models are presented, evidencing advantages and drawbacks of the proposed methodology over more traditional approaches. A case study is then presented, modeled, and the results are compared with those stemming from established formulations.